2022
DOI: 10.3390/nu14194070
|View full text |Cite
|
Sign up to set email alerts
|

Food Fortification of Instant Pulse Porridge Powder with Improved Iron and Zinc Bioaccessibility Using Roselle Calyx

Abstract: Undernutrition and mineral deficiencies negatively impact both the health and academic performance of school children, while diets high in phytic acid and some phenolics inhibit the absorption of minerals such as iron and zinc. This study developed instant porridge powders rich in iron and zinc using pregelatinized chickpea flour (PCPF) and pregelatinized foxtail millet flour (PFMF) and assessed the potential of utilizing roselle calyx powder (RCP) as a source of organic acids to enhance its iron and zinc bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Furthermore, mineral zinc (2.73 mg/100g), calcium (174.48 mg/100 g), iodine (335.97 mg/100 g) and iron (2.9 mg/100 g) were also contained in instant porridge (Table 2). This result was lower than the mineral-supplemented instant pulse porridge powder reported by Subedi et al (2022), where instant pulse porridge contains carbohydrates (66.67%), protein (20.15%), fat (15%), ash (4.40%), energy (458kcal), iron (4.89 mg/100 g) and zinc (3.95 mg/100 g). Calcium deficiency has detrimental effects on immunity and bone health.…”
Section: Nutritional Composition Of Instant Porridgementioning
confidence: 60%
“…Furthermore, mineral zinc (2.73 mg/100g), calcium (174.48 mg/100 g), iodine (335.97 mg/100 g) and iron (2.9 mg/100 g) were also contained in instant porridge (Table 2). This result was lower than the mineral-supplemented instant pulse porridge powder reported by Subedi et al (2022), where instant pulse porridge contains carbohydrates (66.67%), protein (20.15%), fat (15%), ash (4.40%), energy (458kcal), iron (4.89 mg/100 g) and zinc (3.95 mg/100 g). Calcium deficiency has detrimental effects on immunity and bone health.…”
Section: Nutritional Composition Of Instant Porridgementioning
confidence: 60%
“…While spray drying requires less time and typically retains sensitive substances such as color and nutrition, our study found that it resulted in the highest carotenoid content, likely due to the short drying time and protective effect of the carrier material. Few studies have explored the impact of various drying methods on mineral elements, and our findings indicate that drying has little effect on the content of seven mineral elements except for sodium and zinc [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic contents (TPCs), total flavonoid contents (TFCs), and total tannin contents (TTCs) were determined with the well-establish protocols as previously detailed [32,33]. In brief, TPCs and TTCs were measured using Folin-Ciocalteu reagent and recorded at 765 and 700 nm, respectively.…”
Section: Sample Extraction and Determination Of Phytochemicalsmentioning
confidence: 99%